Organic-inorganic hybrid halogen compound molecular solid electrolyte, preparation thereof and all-solid-state battery
By using organic and inorganic hybrid halogen compound molecules to prepare solid electrolytes, the problem of low storage stability of sulfide-type electrolytes in the atmosphere is solved, high ionic conductivity and excellent air stability are achieved, and the safety and stability of the battery are improved.
Patent Information
- Application Number
- CN202411984422.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-31
AI Technical Summary
Existing sulfide-type solid electrolytes usually contain phosphorus elements, which react with moisture and oxygen in the atmosphere, resulting in poor performance and low storage stability in the atmosphere.
Organic and inorganic hybrid halogen compound molecules are used as solid electrolytes and prepared by sintering and ball milling processes to form electrolyte materials with high ionic conductivity, good flexibility and processability, and excellent air stability.
High ionic conductivity and excellent air stability are achieved, lithium dendrites are inhibited, the safety and stability of the battery are improved, and the electrolyte can operate at high current density.
Smart Images

Figure CN119742430A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of energy storage batteries, and in particular relates to a solid electrolyte of organic-inorganic hybrid halogen compound molecules and a preparation method thereof and an all-solid-state battery. Background Art
[0002] In recent years, due to the rapid development of electronic devices such as electric vehicles, computers, and smart phones, traditional liquid electrolyte lithium-ion batteries have been unable to meet people's stringent requirements for high energy density and high safety, and their uses are limited. Therefore, scholars and businessmen have focused their attention on all-solid-state batteries in order to break through the bottleneck of electrochemical energy storage technology and meet future development needs. From a long-term perspective, the energy density and thermal stability of solid-state batteries are significantly better than those of liquid lithium-ion batteries, and they have more long-term commercial prospects.
[0003] Currently, academia and industry are continuously researching the following batteries: from the perspective of capacity, metal-air batteries are studied, which have a theoretical capacity equivalent to that of lithium secondary batteries; from the perspective of safety, non-flammable all-solid-state batteries are studied; from the perspective of power output, supercapacitors are studied; from the perspective of large-scale development, NaS batteries or RFBs (redox flow batteries) are studied; from the perspective of miniaturization, thin-film batteries are studied; and so on.
[0004] Among them, all-solid-state batteries are batteries that replace the liquid electrolyte used in conventional lithium secondary batteries with solid electrolytes. Since no flammable solvents are used in the battery, the safety is greatly improved. At present, solid-state batteries are mainly composed of positive electrodes, negative electrodes, and solid electrolytes. Solid-state batteries can be divided into three categories according to the electrolyte material: polymer solid-state batteries, sulfide solid-state batteries, and oxide solid-state batteries. Polymer solid-state batteries have good safety performance, sulfide solid-state batteries are easy to process, and oxide solid-state batteries have the highest conductivity. But the most advanced solid electrolyte is a sulfide-type solid electrolyte, the ionic conductivity of which has developed to a level close to that of an organic electrolyte solution. However, according to known conditions, sulfide-type solid electrolytes usually contain phosphorus (P), which reacts with moisture and oxygen in the atmosphere, resulting in poor performance, and have low storage stability in the atmosphere, so they are difficult to handle. Summary of the invention
[0005] In view of the above reasons, the purpose of the present invention is to provide a solid electrolyte containing organic-inorganic hybrid halogen compound molecules, the preparation process of which is simple and efficient, and the preparation method is first sintering and then ball milling, which is conducive to expanding production. This series of electrolyte materials has high ionic conductivity, good flexibility and processability, and excellent air stability. The battery composed of the solid electrolyte material of the present invention has excellent electrochemical properties and has great application prospects in all-solid-state lithium metal batteries, thereby solving the technical problems in the prior art that sulfide-type solid electrolytes usually contain phosphorus elements, which will react with moisture and oxygen in the atmosphere, resulting in poor performance, and low storage stability in the atmosphere.
[0006] According to a first aspect of the present invention, an organic-inorganic hybrid halogen compound molecular solid electrolyte is provided, wherein the organic-inorganic hybrid halogen compound molecular solid electrolyte has a chemical formula of M a N b+e Q c X d Y a+bn+cq+dx Z en or M a N 2b+ e Q c X d Y a+cq+dx Z en O bn ;
[0007] Wherein M is selected from one of methylamine, ethylamine, propylamine, butylamine, aniline, benzylamine, and phenylethylamine; N, Q, and X are different metal elements; N is selected from one of Li, Na, K, Ca, Mg, Zn, Al, and Fe; Q is selected from one of Sc, Y, Al, Ga, In, Tl, Ge, Sn, Pb, Sb, and Bi; and X is selected from one of Fe, Zn, Ge, Zr, Ca, Mg, Ba, Bi, Ti, V, Cr, Co, Mn, Ni, Nb, Mo, Tc, Ru, Rh, Pd, Cd, Hf, Ta, W, Re, Os, Ir, and Sn;
[0008] Y is selected from one of F, Cl, Br and I;
[0009] Z is a pseudohalide ion selected from CN - SH - 、OCN - 、SCN - 、SeCN - 、N3 - 、C(CN)3 - CF3SO3 - One of;
[0010] The value ranges of a, b, c, d, and e are: 0 < a ≤ 3, 0 < b ≤ 3, 0 < c ≤ 1, 0 < d ≤ 1, 0 < e ≤ 6; n, q, and x are the numerical values of the valences of element N, element Q, and element X, respectively.
[0011] Preferably, the organic-inorganic hybrid halide molecular solid electrolyte is in powder form.
[0012] According to another aspect of the present invention, there is provided a method for preparing the organic-inorganic hybrid halide molecular solid electrolyte. In an inert gas atmosphere, the precursors MY, NY n , QY q , XY x , NZ n or MY, N2O n , QY q , XY x , NZ n are mixed in a molar ratio of a:b:c:d:e, and after ball milling and sintering, the chemical general formula obtained is M a N b+e Q c X d Y a+bn+cq+dx Z en or M a N 2b+e Q c X d Y a+cq+dx Z en O bn ;
[0013] wherein M is selected from one of methylamine, ethylamine, propylamine, butylamine, aniline, benzylamine, and phenethylamine; N, Q, and X are different metal elements; N is selected from one of Li, Na, K, Ca, Mg, Zn, Al, and Fe; Q is selected from one of Sc, Y, Al, Ga, In, Tl, Ge, Sn, Pb, Sb, and Bi; X is selected from one of Fe, Zn, Ge, Zr, Ca, Mg, Ba, Bi, Ti, V, Cr, Co, Mn, Ni, Nb, Mo, Tc, Ru, Rh, Pd, Cd, Hf, Ta, W, Re, Os, Ir, and Sn;
[0014] Y is selected from one or more of F, Cl, Br, and I;
[0015] Z is a pseudohalide ion and is selected from CN - , SH - , OCN - , SCN - , SeCN - , N3 - , C(CN)3 - , CF3SO3- one of the following;
[0016] The value ranges of a, b, c, d, and e are: 0 < a ≤ 3, 0 < b ≤ 3, 0 < c ≤ 1, 0 < d ≤ 1, 0 < e ≤ 6; n, q, and x are the numerical values of the valence of element N, element Q, and element X, respectively.
[0017] Preferably, the mass ratio of balls to materials in the ball milling is (10 - 40):1.
[0018] Preferably, the rotation speed of the ball milling is 100 - 1000 r / min.
[0019] Preferably, the time of the ball milling is 2 - 48 h.
[0020] Preferably, the sintering temperature is 100 - 700 °C, and the sintering time is 1 - 12 h.
[0021] Preferably, the sintering is carried out under vacuum conditions, or under argon or nitrogen conditions.
[0022] According to another aspect of the present invention, a all-solid-state battery is provided, including the organic-inorganic hybrid halogen compound molecular solid electrolyte described above.
[0023] Compared with the prior art by the above technical solutions conceived by the present invention, the following technical advantages are mainly possessed:
[0024] (1) The main purpose of the present invention is to provide a solid electrolyte of an organic-inorganic hybrid halogen compound, which improves the uniform distribution of halogen element X inside the crystal grains and avoids the formation of a LiX coating layer on the crystal grain surface; moreover, metastable halogen X (X = F, Cl, Br) atoms accompany Li atoms to in-situ precipitate LiX particles, which are diffusely distributed at the grain boundaries, thereby inhibiting the deposition and growth of metallic lithium inside the electrolyte, enhancing the ability of the electrolyte to inhibit lithium dendrites, and enabling the electrolyte to work at a high current density. In this way, both the high ionic conductivity of the battery can be maintained, and its safety and stability can be improved.
[0025] (2) The present invention dopes organic substances into the halogen solid electrolyte, which can improve the performance of the electrolyte through various mechanisms, including increasing the ionic conductivity, enhancing the mechanical properties, improving the chemical stability, broadening the electrochemical window, and improving the interface compatibility, thus playing an important role in high-performance battery systems.
[0026] (3) By introducing organic amine compounds, a conductive channel can be formed, thereby increasing the migration rate of lithium ions and further improving the conductivity of the electrolyte. By introducing organic molecules, the flexibility and plasticity of the electrolyte can be increased, so that it can still maintain good shape and structural stability under high temperature or high pressure conditions. Moreover, certain organic compounds can form stable complexes with halogens, thereby preventing the electrolyte from decomposing in high temperature or humid environments, and improving chemical stability. The presence of organic matter can broaden the electrochemical window of halogen solid electrolytes, making them stable over a wider voltage range, making them suitable for higher voltage battery systems. Doping with organic matter can improve the interface compatibility between halogen solid electrolytes and electrode materials, reduce interface resistance, and thus improve the overall performance of the battery.
[0027] (4) The present invention can effectively adjust the lattice parameters in the halide solid electrolyte, improve the lithium ion transmission channel and enhance the ion conductivity by doping different types of metal elements. At the same time, the halide electrolyte material doped with metal elements has good air stability and structural stability, and can maintain long-term chemical stability in a dew point environment of -40°C.
[0028] (5) The pseudohalide ion in the present invention refers to an anion having properties such as ionic radius similar to those of a halide ion. Compared with a halide ion, the compound formed by the pseudohalide ion is not easy to absorb water and deliquesce, thereby greatly reducing the humidity instability caused by the halide ion, making the electrolyte have excellent long-term stability and humidity stability, and is easier to form and maintain a thin sheet state. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The MALi2In prepared in accordance with Examples 1-4 of the present invention 0.1 Fe 0.1 Cl 2.5 CN、MALi2In 0.1 Zr 0.1 Cl 2.7 OCN、MALi2Ge 0.1 Fe 0.1 Cl 2.7 SCN, (MA)2Li5Sn 0.5 Ge 0.5 XRD pattern of Cl7(CN)3.
[0030] Figure 2 This is the impedance diagram of the solid electrolyte prepared in Example 1 of the present invention. The room temperature ionic conductivity of Example 1 is 2.9×10 -3 S cm -1 .
[0031] Figure 3The impedance diagram of the solid electrolyte prepared in Example 4 of the present invention is shown in FIG. 1 . The room temperature ionic conductivity of Example 4 is 3.2×10 -3 S cm -1 . DETAILED DESCRIPTION
[0032] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0033] In the present invention, M is selected from methylamine (MA), ethylamine (Ethylamine), propylamine (Propylamine), butylamine (Butylamine), aniline (Aniline), benzylamine (Benzylamine), phenylethylamine (β-Phenylethylamine).
[0034] In the present invention, N, Q and X are different metal elements; N is selected from one of Li, Na, K, Ca, Mg, Zn, Al and Fe; Q is selected from one of Sc, Y, Al, Ga, In, Tl, Ge, Sn, Pb, Sb and Bi; X is selected from one of Fe, Zn, Ge, Zr, Ca, Mg, Ba, Bi, Ti, V, Cr, Co, Mn, Ni, Nb, Mo, Tc, Ru, Rh, Pd, Cd, Hf, Ta, W, Re, Os, Ir and Sn; and Y is selected from one of F, Cl, Br and I.
[0035] In the present invention, Z is a pseudohalide ion selected from cyanate ion (CN - ), hydrogen sulfide ion (SH - ), oxycyanate ion (OCN - ), thiocyanate ion (SCN - ), selenocyanate ion (SeCN - ), azide (N3 - ), cyanoformyl radical (C(CN)3 - ), trifluoromethanesulfonate (CF3SO3 - )
[0036] The following are specific embodiments
[0037] Example 1
[0038] This embodiment provides a solid electrolyte MALi2In of an organic-inorganic hybrid halogen compound molecule. 0.1 Fe 0.1Cl 2.5 CN, the specific preparation method is as follows:
[0039] (1) In an Ar atmosphere glove box, weigh MACl, LiCl, InCl3, FeCl2, and LiCN precursor powders according to the molar ratio of 1:1:0.1:0.1:1, place them in an agate mortar, and grind them by hand using an agate pestle for 20 min; add the ground precursor powders into a ZrO2 ball mill with a ball-to-material mass ratio of 20:1, transfer the ball mill to a ball mill, and ball mill at 500 rpm for 10 h, then allow it to cool naturally to room temperature.
[0040] (2) The milled powder is taken out from the ball mill and stored in an argon glove box. The powder is placed in a quartz glass tube under an argon environment, which is evacuated and sealed. The quartz tube is then transferred to a muffle furnace and sintered at 300° C. for 2 h. The temperature is naturally cooled to room temperature, the quartz tube is taken out, and the material is transferred to an argon glove box and ground into powder until it is uniform to obtain a solid electrolyte.
[0041] MALi2In 0.1 Fe 0.1 Cl 2.5 CN.
[0042] Example 2
[0043] This embodiment provides a solid electrolyte MALi2In of an organic-inorganic hybrid halogen compound molecule. 0.1 Zr 0.1 Cl 2.7 OCN, the specific preparation method is as follows:
[0044] (1) In an Ar atmosphere glove box, weigh MACl, LiCl, InCl3, ZrCl4, and LiOCN precursor powders according to the molar ratio of 1:1:0.1:0.1:1, place them in an agate mortar, and grind them by hand using an agate pestle for 20 min; add the ground precursor powders into a ZrO2 ball mill with a ball-to-material mass ratio of 20:1, transfer the ball mill to a ball mill, and ball mill at 500 rpm for 10 h, then allow it to cool naturally to room temperature.
[0045] (2) The milled powder is taken out from the ball mill and stored in an argon glove box. The powder is placed in a quartz glass tube under an argon environment, which is evacuated and sealed. The quartz tube is then transferred to a muffle furnace and sintered at 300° C. for 2 h. The temperature is naturally cooled to room temperature, the quartz tube is taken out, and the material is transferred to an argon glove box and ground into powder until it is uniform to obtain a solid electrolyte.
[0046] MALi2In 0.1 Zr 0.1 Cl2.7 OCN.
[0047] Example 3
[0048] This embodiment provides a solid electrolyte MALi2Ge of organic-inorganic hybrid halogen compound molecules 0.1 Fe 0.1 Cl 2.7 SCN, the specific preparation method is as follows:
[0049] (1) In an Ar atmosphere glove box, weigh MACl, LiCl, GeCl4, FeCl3, and LiSCN precursor powders according to the molar ratio of 1:1:0.1:0.1:1, place them in an agate mortar, and grind them by hand using an agate pestle for 20 min; add the ground precursor powders into a ZrO2 ball mill with a ball-to-material mass ratio of 20:1, transfer the ball mill to a ball mill, and ball mill at 500 rpm for 10 h, then allow it to cool naturally to room temperature.
[0050] (2) The milled powder is taken out from the ball mill and stored in an argon glove box. The powder is placed in a quartz glass tube under an argon environment, which is evacuated and sealed. The quartz tube is then transferred to a muffle furnace and sintered at 300° C. for 2 h. The temperature is naturally cooled to room temperature, the quartz tube is taken out, and the material is transferred to an argon glove box and ground into powder until it is uniform to obtain a solid electrolyte.
[0051] MALi2Ge 0.1 Fe 0.1 Cl 2.7 SCN.
[0052] Example 4
[0053] This embodiment provides a solid electrolyte (MA)2Li5Sn2O3 of organic-inorganic hybrid halogen compound molecules. 0.5 Ge 0.5 Cl7(CN)3, the specific preparation method is as follows:
[0054] (1) In an Ar atmosphere glove box, weigh MACl, LiCl, SnCl2, GeCl4, and LiCN precursor powders according to the molar ratio of 2:2:0.5:0.5:3, place them in an agate mortar, and grind them by hand using an agate pestle for 20 min; add the ground precursor powders into a ZrO2 ball mill with a ball-to-material mass ratio of 20:1, transfer the ball mill to a ball mill, and ball mill at 500 rpm for 10 h, then allow it to cool naturally to room temperature.
[0055] (2) The milled powder was taken out from the ball mill and stored in an argon glove box. The powder was placed in a quartz glass tube under an argon environment, which was evacuated and sealed. The quartz tube was then transferred to a muffle furnace and sintered at 300 °C for 2 h. The temperature was naturally cooled to room temperature, the quartz tube was taken out, and the material was transferred to an argon glove box and ground into powder until it was uniform to obtain a solid electrolyte (MA)2Li5Sn 0.5 Ge 0.5 Cl7(CN)3.
[0056] Example 5
[0057] According to Examples 1-4, the difference between this example and Example 4 is that the ratio of the type and amount of the precursor powder is: BACl, LiCl, YCl3, NbCl5, LiCN = 2:2:0.5:0.5:3, hand grinding for 20 minutes, the ball-to-material mass ratio is 20:1, the ball milling speed is 500rpm, the ball milling time is 10h, the sintering temperature is 300℃, and the sintering time is 2h. The other operations are the same as those in Example 4 to obtain a solid electrolyte (BA)2Li5Y 0.5 Nb 0.5 Cl8(CN)3.
[0058] Example 6
[0059] The difference between this embodiment and embodiment 4 is that the ratio of the type and amount of the precursor powder is: PEACl, LiCl, SbCl5, CrCl6, LiSCN = 2:2:0.5:0.5:3, hand grinding for 20 minutes, the ball-to-material mass ratio is 20:1, the ball milling speed is 600rpm, the ball milling time is 10h, the sintering temperature is 350℃, and the sintering time is 2h. The other operations are the same as those in embodiment 4 to obtain a solid electrolyte (PEA)2Li5Sb 0.5 Cr 0.5 Cl 9.5 (SCN)3.
[0060] Example 7
[0061] The difference between this embodiment and embodiment 4 is that the ratio of the type and amount of the precursor powder is: MACl, LiCl, ScCl3, BiCl3, LiCF3SO3 = 3:3:1:1:6, hand grinding for 20 minutes, the ball-to-material mass ratio is 20:1, the ball milling speed is 600rpm, the ball milling time is 10h, the sintering temperature is 350℃, and the sintering time is 3h. The other operations are the same as those in embodiment 4 to obtain a solid electrolyte (MA)3Li9ScBiCl 12 (CF3SO3)6.
[0062] Example 8
[0063] The difference between this embodiment and embodiment 4 is that the ratio of the type and amount of the precursor powder is: BACl, LiCl, YCl3, TiCl4, LiOCN = 3:3:1:1:6, hand grinding for 20 minutes, the ball-to-material mass ratio is 25:1, the ball milling speed is 700rpm, the ball milling time is 15h, the sintering temperature is 400℃, and the sintering time is 3h. The other operations are the same as those in embodiment 4 to obtain a solid electrolyte (BA)3Li9YTiCl 13 (OCN)6.
[0064] Example 9
[0065] The difference between this embodiment and embodiment 4 is that the ratio of the types and amounts of the precursor powders is: PEACl, LiCl, AlCl3, TaCl 5、 LiCN=1:2:0.3:0.7:3, hand milling for 20 min, ball-to-material mass ratio of 25:1, ball milling speed of 700 rpm, ball milling time of 15 h, sintering temperature of 400 °C, sintering time of 3 h. Other operations are the same as those in Example 4 to obtain a solid electrolyte PEALi5Al 0.3 Ta 0.7 Cl 7.4 (CN)3.
[0066] Example 10
[0067] The difference between this embodiment and embodiment 4 is that the ratio of the type and amount of the precursor powder is: MACl, LiCl, ZnCl2, FeCl2, LiSH = 1:2:0.3:0.7:3, hand grinding for 20 minutes, the ball-to-material mass ratio is 25:1, the ball milling speed is 750rpm, the ball milling time is 15h, the sintering temperature is 450℃, and the sintering time is 5h. The other operations are the same as those in embodiment 4 to obtain a solid electrolyte MALi5Zn 0.3 Fe 0.7 Cl5(SH)3.
[0068] Embodiment 11
[0069] The difference between this embodiment and embodiment 4 is that the ratio of the type and amount of the precursor powder is: BACl, MgCl2, GaCl3, CoCl2, Mg(SeCN)2=2:1:0.6:0.4:5, hand grinding for 20 min, ball-to-material mass ratio of 30:1, ball milling speed of 750 rpm, ball milling time of 20 h, sintering temperature of 450 ° C, sintering time of 5 h. The other operations are the same as those in embodiment 4 to obtain a solid electrolyte (BA)2Mg6Ga 0.6 Co 0.4 Cl6(SeCN)5.
[0070] Example 12
[0071] The difference between this embodiment and embodiment 4 is that the ratio of the type and amount of the precursor powder is: MAF, LiF, InF3, FeF3, LiCN = 2:1:0.6:0.4:5, hand grinding for 20 minutes, the ball-to-material mass ratio is 30:1, the ball milling speed is 800rpm, the ball milling time is 20h, the sintering temperature is 500℃, and the sintering time is 5h. The other operations are the same as those in embodiment 4 to obtain the solid electrolyte (MA)2Li6In 0.6 Fe 0.4 F6(CN)5.
[0072] Example 13
[0073] The difference between this embodiment and embodiment 4 is that the ratio of the type and amount of the precursor powder is: MACl, Li2O, InCl3, FeCl2, LiCN = 1:2:0.4:0.6:3, hand grinding for 20 minutes, the ball-to-material mass ratio is 30:1, the ball milling speed is 800rpm, the ball milling time is 20h, the sintering temperature is 500℃, and the sintering time is 5h. The other operations are the same as those in embodiment 4 to obtain the solid electrolyte MALi7In 0.4 Fe 0.6 Cl 3.4 (CN)3O2.
[0074] Embodiment 14
[0075] The difference between this embodiment and embodiment 4 is that the ratio of the type and amount of the precursor powder is: MACl, MgO, InCl3, FeCl3, Mg(CN)2=1:2:0.3:0.7:3, hand grinding for 20 min, the ball-to-material mass ratio is 30:1, the ball milling speed is 800 rpm, the ball milling time is 20 h, the sintering temperature is 500 ° C, and the sintering time is 5 h. The other operations are the same as those in embodiment 4 to obtain the solid electrolyte MAMg5In 0.3 Fe 0.7 Cl4(CN)6O2.
[0076] Embodiment 15
[0077] The difference between this embodiment and embodiment 4 is that the ratio of the type and amount of the precursor powder is: MACl, Al2O3, GeCl4, FeCl2, Al(CN)3=2:1:0.6:0.4:3, hand grinding for 20 min, ball-to-material mass ratio of 30:1, ball milling speed of 800 rpm, ball milling time of 20 h, sintering temperature of 500 ° C, sintering time of 5 h. The other operations are the same as those in embodiment 4 to obtain a solid electrolyte (MA)2Al5Ge0.6 Fe 0.4 Cl 5.2 (CN)9O3.
[0078] Performance Testing
[0079] like Figure 1 As shown, the samples MALi2In obtained in Examples 1-4 0.1 Fe 0.1 Cl 2.5 CN、MALi2In 0.1 Zr 0.1 Cl 2.7 OCN、MALi2Ge 0.1 Fe 0.1 Cl 2.7 SCN, (MA)2Li5Sn 0.5 Ge 0.5 The XRD data of Cl7(CN)3 showed that the main body of the material was in a crystalline phase.
[0080] like Figure 2 As shown, the sample MALi2In obtained in Example 1 0.1 Fe 0.1 Cl 2.5 The ionic conductivity of CN can reach 2.9×10 -3 Scm -1 .
[0081] like Figure 3 As shown, the sample (MA)2Li5Sn obtained in Example 4 0.5 Ge 0.5 The ionic conductivity of Cl7(CN)3 can reach 3.2×10 -3 S cm -1 .
[0082] Weigh 100 mg of electrolyte powder and place it in a special solid-state battery stainless steel mold with a diameter of 10 mm. Press it at a pressure of 380 MP, hold the pressure for 1 minute, and then take it out. The room temperature ionic conductivity of the solid electrolyte in each embodiment is tested by the blocking electrode test method. The test frequency is 0.1 Hz to 1 MHz, and the calculation formula is σ = d / (SR), where d is the thickness of the electrolyte, S is the area of the electrolyte side that contacts the blocking electrode, and R is the resistance obtained according to the AC impedance test. Please refer to Table 1 for the room temperature ionic conductivity of each embodiment.
[0083] Using the MALi2In obtained in Example 1 0.1 Fe 0.1 Cl 2.5 CN solid electrolyte assembled full battery. The positive electrode is nickel manganese cobalt lithium material LiNi 0.5 Mn0.3 Co 0.2 Composite electrode of O2 and Li6 PS5 Cl, the electrolyte layer is MALi2In 0.1 Fe 0.1 Cl 2.5 CN, and the negative electrode was a Li-In-Li6 PS5 Cl composite electrode to prepare an all-solid-state lithium-ion battery, which was then charged and discharged at a rate of 0.2C.
[0084] Table 1 Summary of test results
[0085]
[0086]
[0087] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. An organic-inorganic hybrid halogen compound molecular solid electrolyte, characterized in that: The chemical formula of the organic-inorganic hybrid halogen compound molecular solid electrolyte is M a N b+e Q c X d Y a+bn+cq+dx Z en or M a N 2b+e Q c X d Y a+cq+dx Z en O bn ; Wherein M is selected from one of methylamine, ethylamine, propylamine, butylamine, aniline, benzylamine, and phenethylamine; N, Q, and X are different metal elements; N is selected from one of Li, Na, K, Ca, Mg, Zn, Al, and Fe; Q is selected from one of Sc, Y, Al, Ga, In, Tl, Ge, Sn, Pb, Sb, and Bi; X is selected from one of Fe, Zn, Ge, Zr, Ca, Mg, Ba, Bi, Ti, V, Cr, Co, Mn, Ni, Nb, Mo, Tc, Ru, Rh, Pd, Cd, Hf, Ta, W, Re, Os, Ir, and Sn; Y is selected from one of F, Cl, Br, and I; Z is a pseudohalide ion selected from CN - SH - 、OCN - 、SCN - 、SeCN - 、N3 - 、C(CN)3 - CF3SO3 - One of; The value ranges of a, b, c, d, and e are: 0 < a ≤ 3, 0 < b ≤ 3, 0 < c ≤ 1, 0 < d ≤ 1, 0 < e ≤ 6; n, q, and x are the numerical values of the valence of N element, Q element, and X element respectively.
2. The organic-inorganic hybrid halogen compound molecular solid electrolyte according to claim 1, characterized in that: The organic-inorganic hybrid halogen compound molecular solid electrolyte is in powder form.
3. The method for preparing the organic-inorganic hybrid halogen compound molecular solid electrolyte according to claim 1 or 2, characterized in that: In a protective gas atmosphere, the precursors MY and NY n , QY q , XY x , NZ n Or precursor MY, N2O n , QY q , XY x , NZ n The mixture is mixed in the molar ratio of a:b:c:d:e, and after ball milling and sintering, the obtained chemical formula is M a N b+e Q c X d Y a+bn+cq+dx Z en or M a N 2b+e Q c X d Y a+cq+dx Z en O bn ; Wherein M is selected from one of methylamine, ethylamine, propylamine, butylamine, aniline, benzylamine, and phenethylamine; N, Q, and X are different metal elements; N is selected from one of Li, Na, K, Ca, Mg, Zn, Al, and Fe; Q is selected from one of Sc, Y, Al, Ga, In, Tl, Ge, Sn, Pb, Sb, and Bi; X is selected from one of Fe, Zn, Ge, Zr, Ca, Mg, Ba, Bi, Ti, V, Cr, Co, Mn, Ni, Nb, Mo, Tc, Ru, Rh, Pd, Cd, Hf, Ta, W, Re, Os, Ir, and Sn; Y is selected from one or more of F, Cl, Br, and I; Z is a pseudohalide ion selected from CN - SH - 、OCN - 、SCN - 、SeCN - 、N3 - 、C(CN)3 - CF3SO3 - One of; The value ranges of a, b, c, d, and e are: 0 < a ≤ 3, 0 < b ≤ 3, 0 < c ≤ 1, 0 < d ≤ 1, 0 < e ≤ 6; n, q, and x are the numerical values of the valence of N element, Q element, and X element respectively.
4. The preparation method according to claim 3, characterized in that: The mass ratio of balls to materials in the ball milling is (10 - 40):
1.
5. The preparation method according to claim 3, characterized in that: The rotation speed of the ball milling is 100 - 1000 r / min.
6. The preparation method according to claim 3, characterized in that: The time of the ball milling is 2 - 48 h.
7. The preparation method according to claim 3, characterized in that: The sintering temperature is 100 - 700 °C, and the sintering time is 1 - 12 h.
8. The preparation method according to claim 3, characterized in that: The sintering is carried out under vacuum conditions, or under argon or nitrogen conditions.
9. An all-solid-state battery, characterized in that: It includes the organic-inorganic hybrid halogen compound molecular solid electrolyte described in any one of claims 1 - 2.
Citation Information
Patent Citations
Flexible organic-inorganic hybrid solid electrolyte, preparation method thereof and battery
CN113675461A
Metal element doped halide solid electrolyte material and preparation method and application thereof
CN115275330A
Halide solid electrolyte as well as preparation method and application thereof
CN116581367A
Solid electrolyte and lithium ion battery
CN117878389A
Diaphragm Pump with Multiple Discharging Pipes
KR102549725B1
Cited By
Solid electrolyte material and preparation method and application thereof
CN121748511A